Transformation of Malaysian Shop Office and The Impact of Visual Comfort - Tan, Hui Ping; Abdul Majid, Roshida (Jurnal Koridor, 2023)
This paper investigates the transformation of Malaysian shop offices over the last few decades, and the impact of visual comfort on their design and functionality. Shop offices are a prevalent building type in Malaysia, combining commercial and office spaces in the same structure. The rise of e-commerce and the need for visually appealing and functional spaces has driven the transformation in shop office design. This study examines the historical context of shop offices in Malaysia, the factors driving their transformation, and the concept of visual comfort, including its various elements. The study then analyzes the impact of visual comfort on the design and functionality of modern shop offices in Malaysia. The research findings provide insights into the importance of visual comfort in commercial space design and the factors driving the evolution of shop office design in Malaysia. Finally, the paper identifies challenges and opportunities for the continued development of visually appealing and functional shop offices in Malaysia.